Right and Left Ventricular Diastolic Pressure–Volume Relations: A Comprehensive Review - Pasipoularides, Ares (Journal of cardiovascular translational research, 2013)
Ventricular compliance alterations can affect cardiac performance and adaptations. Moreover, diastolic mechanics are important in assessing both diastolic and systolic function, since any filling impairment can compromise systolic function. A sigmoidal passive filling pressure–volume relationship, developed using chronically instrumented, awake-animal disease models, is clinically adaptable to evaluating diastolic dynamics using subject-specific micromanometric and volumetric data from the entire filling period of any heartbeat(s). This innovative relationship is the global, integrated expression of chamber geometry, wall thickness, and passive myocardial wall properties. Chamber and myocardial compliance curves of both ventricles can be computed by the sigmoidal methodology over the entire filling period and plotted over appropriate filling pressure ranges. Important characteristics of the compliance curves can be examined and compared between the right and the left ventricle and for different physiological and pathological conditions. The sigmoidal paradigm is more accurate and, therefore, a better alternative to the conventional exponential pressure–volume approximation.